2002
DOI: 10.1002/jbm.a.10402
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization and tissue infiltration of a biodegradable polyurethane matrix

Abstract: Urethanes are frequently used in biomedical applications because of their excellent biocompatibility. However, their use has been limited to bioresistant polyurethanes. The aim of this study was to develop a nontoxic biodegradable polyurethane and to test its potential for tissue compatibility. A matrix was synthesized with pentane diisocyanate (PDI) as a hard segment and sucrose as a hydroxyl group donor to obtain a microtextured spongy urethane matrix. The matrix was biodegradable in an aqueous solution at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Foreign-body giant cells did accumulate around the polymer and in its pores, suggesting the degradation is facilitated by hydrolysis as well as by giant cells. More important, subcutaneous implants of the polymer allowed infiltration of vascular and connective tissue, suggesting the free flow of fluids and nutrients in the implants (7,14). The osteogenic tissue presence in the polymer surface and the membrane incorporation in the newly formed bone tissue were related (4,17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Foreign-body giant cells did accumulate around the polymer and in its pores, suggesting the degradation is facilitated by hydrolysis as well as by giant cells. More important, subcutaneous implants of the polymer allowed infiltration of vascular and connective tissue, suggesting the free flow of fluids and nutrients in the implants (7,14). The osteogenic tissue presence in the polymer surface and the membrane incorporation in the newly formed bone tissue were related (4,17).…”
Section: Discussionmentioning
confidence: 98%
“…The PTFE barriers have enough firmness against the soft tissue pressure, an important requirement for bone regeneration. The castor oil polyurethanes present an excellent biological compatibility (12)(13)(14). The observations on the inflammatory infiltrate in the samples treated with polyurethane barrier, showed an initial inflammatory reaction which decreased along the time (4), and the presence of inflammatory multinuclear giant cells (IMGC) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported vascularizaton of tissue engineered constructs using both synthetic and naturally-derived constructs containing growth factors and/or cells (for examples see (Borges et al, 2003a;Borges et al, 2003b;Elcin and Elcin, 2006;Ganta et al, 2003;Kaigler et al, 2006;Murphy et al, 2004;Tanihara et al, 2001;Yao et al, 2004;Zisch et al, 2003)). However, the primary focus of these studies did not address the manner of directed vascular invasion into the matrix, but only upon the end extent of vacularization.…”
Section: Discussionmentioning
confidence: 99%
“…Polyol and sebacic acid are both endogenous monomers found in human metabolites (Ellwood [1995]; Natah et al [1997]; Sestoft [1985]); hence, PPSs generally show little toxicity to host tissues (Chen et al [2011a]; Wang et al [2003]). Poly(glycerol sebacate) (PGS) is the most extensively evaluated member of the PPS family, with most in vitro data demonstrating that PGS has a very good biocompatibility (Fidkowski et al [2005a]; Gao et al [2007]; Motlagh et al [2006]; Sundback et al [2005]; Sundback et al [2004]; Wang [2004]). Poly(xylitol sebacate) (PXS) has also been developed using xylitol, a well-studied monomer in terms of biocompatibility and pharmacokinetics in humans (Ellwood [1995]; Natah et al [1997]; Sestoft [1985]; Talke and Maier [1973]).…”
Section: Biodegradable Chemically Cross-linked Elastomersmentioning
confidence: 99%